Study The Link Between Accounting and Taxation Practice in Vietnam - Anh Tuan Nguyen; Tung Dao Nguyen; Hien Thu Nguyen (Journal of Accounting and Taxation, 2021)
The objective of the study is to analyze and evaluate the link between accounting and taxation through the synthesis of domestic and foreign studies, combined with analysis of specific regulations in Vietnam. The study identifies 11 contents that have an interference between accounting and tax to conduct surveys in enterprises. After analyzing and explaining the survey results, the researcher decides to choose 06 representative contents in choosing the rules according to the level (low, medium, high) to conduct the analysis. The research results show that the tendency to choose to use accounting rules higher than tax rules and the link between accounting and taxation in Vietnam is moving to become more independent. At the same time, large enterprises will prefer the use of accounting rules over tax rules and vice versa for small and medium enterprises. Through the results of this research, policy makers can identify the position of the link between accounting and taxation, and then make decisions to adjust the relationship between accounting and taxation appropriately with the integration and development of Vietnam's economy.